1985
DOI: 10.1159/000145949
|View full text |Cite
|
Sign up to set email alerts
|

Fibre Number and Sizes of Mouse Soleus Muscle in Early Postnatal Protein Malnutrition

Abstract: The effect of early postnatal protein malnutrition on the development of soleus muscle was investigated in 26 mice (13 males, 13 females). The control group received a balanced diet containing 18% lactalbumin while the protein-malnourished group received protein deficient diet containing 0.5% lactalbumin. The body weight was determined both at 3 weeks (weaning age) and 12 weeks of age. The soleus muscle weight, total number and sizes of muscle fibres were also determined at 12 weeks of age for each mouse. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
1
9
0
5
Order By: Relevance
“…4 These findings emphasize the importance of nutritional recovery at early phases of life, in order to achieve normal growth and development. [13][14][15] Research demonstrates that maternal protein deficiency at the start or from the second half of gestation affects the body weight and number of muscle fibers in the offspring, observed in studies undertaken with low birth weight rats, dogs and monkeys.…”
Section: Histochemical Parameters: Morphology Differentiation and Mementioning
confidence: 89%
See 1 more Smart Citation
“…4 These findings emphasize the importance of nutritional recovery at early phases of life, in order to achieve normal growth and development. [13][14][15] Research demonstrates that maternal protein deficiency at the start or from the second half of gestation affects the body weight and number of muscle fibers in the offspring, observed in studies undertaken with low birth weight rats, dogs and monkeys.…”
Section: Histochemical Parameters: Morphology Differentiation and Mementioning
confidence: 89%
“…Similar results have been reported by several other authors in their studies of prenatal malnutrition. 4 It has also been observed that protein malnutrition statistically reduces the muscle tissue weight. This is probably due to lost tissue proteins.…”
Section: 516mentioning
confidence: 99%
“…Feed restriction significantly affects the growth and differentiation of cells, and the earlier the malnutrition, the greater the impairment in tissues and organs (Ihemelandu, 1985). Studies in rats, dogs and monkeys showed that protein restriction during pregnancy affects body weight and the number of muscle fibers of offspring (Nascimento et al, 1990;Oliveira et al, 1999;Nunes et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The number of undernourished people in the world is extremely high and reached almost 1 billion in 2010 (FAO, 2010). Malnutrition in developing countries has mostly been attributed to a low protein diet (Ihemelandu, 1985;Ge and Chang, 2001) or a low quality of food consumed (Morgane et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation